If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -6) = 391 Reorder the terms: x(-6 + x) = 391 (-6 * x + x * x) = 391 (-6x + x2) = 391 Solving -6x + x2 = 391 Solving for variable 'x'. Reorder the terms: -391 + -6x + x2 = 391 + -391 Combine like terms: 391 + -391 = 0 -391 + -6x + x2 = 0 Factor a trinomial. (-17 + -1x)(23 + -1x) = 0Subproblem 1
Set the factor '(-17 + -1x)' equal to zero and attempt to solve: Simplifying -17 + -1x = 0 Solving -17 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + -1x = 0 + 17 Combine like terms: -17 + 17 = 0 0 + -1x = 0 + 17 -1x = 0 + 17 Combine like terms: 0 + 17 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17Subproblem 2
Set the factor '(23 + -1x)' equal to zero and attempt to solve: Simplifying 23 + -1x = 0 Solving 23 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -1x = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -1x = 0 + -23 -1x = 0 + -23 Combine like terms: 0 + -23 = -23 -1x = -23 Divide each side by '-1'. x = 23 Simplifying x = 23Solution
x = {-17, 23}
| 7x-1=4x-8(7+x) | | 0.16x+0.1y=0.08 | | 5x(12x-7)-4x(15x-11)=30+29x | | 30x=100+20x | | 3y+6x=36 | | 0.03x+0.09y=-0.27 | | 3(2f+4)=2(3-6) | | 3(5x+3)=36+6x | | -3x^2+7x+6=f(x) | | (x^3-27)(x^3-27)(x^3-27)=0 | | 5x(12x-7)-4x(15x-11)=30-29x | | -1/6(24)= | | 2/3(12)= | | 3c=2c+0 | | f(x)=-3x^2+7x+6 | | 0.15(x-4)=9.9-0.3(x-1) | | 2x+6=6x-6 | | ac+ax=b+6 | | 3=-6n+7n+18 | | 3d-14+6d+9= | | u^2=100 | | 3[a-5]=-6 | | 14+8x=-4+2x | | 4y-7+y+51=6y+50-4y | | x-1+6x=20 | | 3x+4y-7x-7y= | | 3m+(m+1)=6m+1 | | 3e(3e-10)=2 | | 9x(x+2y+3z)= | | 6s^3+23s^2+33s=13s | | 3x-5=5+3x | | y+x^2-2x=0 |